Mental Health in Bhartiya Perspective and its Implications - Parmar, Rita A (INDIAN EDUCATIONAL REVIEW, 2025)
The concept of mental health is comprehensively given in the ancient Bhartiya scriptures like Patanjali Yoga Darshan, Charaka Samhita, Sushruta Samhita, Ashtanga Hrudayam and Shrimad Bhagavad Gita. The Bhartiya perspective is given less priority in current mental health research and practice. This paper focused on the study of mental health from the Bhartiya perspective, and some implications have been drawn. According to the Bhartiya perspective, a person’s mental health is determined by blissfulness, happiness and peace of mind. The analysis reveals that practising the foundations of Bhartiya philosophy of life results in balancing one’s mental health. A person’s philosophy of life has an impact on their mind, way of life and behaviour.